Effects of dietary copper and zinc hydroxychloride supplementation on bone development, skin quality and hematological parameters of broilers chickens - dos Santos, Tatiane S. [UNESP]; Augusto, Karolina V. Z.; Han, Yanming; Sartori, Maria M. P. [UNESP]; Batistioli, Julianna S. [UNESP]; Contin Neto, Armando C. [UNESP]; Ferreira Netto, Raimundo G. [UNESP]; Zanetti, Leonardo H. [UNESP]; Pasquali, Guilherme A. M. [UNESP]; Muro, Everton M. [UNESP]; Araujo, Robert G. A. C. [UNESP]; Basso, Roberta M. [UNESP]; et al. (Wiley, 2023)
This study was carried out to evaluate the effects of supplementation with different levels of copper (Cu) and zinc (Zn), using two mineral sources (sulphate and hydroxy forms), on the bone characteristics, skin strength/elasticity, and haematological parameters of broilers. A total of 1792 1-day-old male Cobb-500 broiler chickens were randomly distributed among eight dietary treatments, using Cu sulphate (CSM) or hydroxychloride (CHC), and Zn sulphate (ZSM) or hydroxychloride (ZHC). The dietary treatments were as follows: (1) low-CSM/high-ZSM, (2) high-CSM/high-ZSM, (3) low-CHC/low-ZHC, (4) low-CHC/medium-ZHC, (5) low-CHC/high-ZHC, (6) high-CHC/low-ZHC, (7) high-CHC/medium-ZHC, and (8) high-CHC/high-ZHC. On Day 42, blood samples were collected from one bird/pen to analyze the haematological parameters. Finally, two birds/pen were slaughtered, and the tibia and femur were collected to analyze the quality of bone and skin. The means were subjected to ANOVA and, when significant, compared by Tukey's test (p < 0.05) or Dunnett's (p < 0.05) test. The haematological parameters were not influenced by mineral supplementation. However, the inclusion of low ZHC enhanced the skin strength compared to high ZHC (p = 0.046). Furthermore, the bone mineral density of the tibia proximal epiphysis, tibia ash and tibia mineral content were positively improved with supplementation of low-CHC/medium-ZHC compared to high-CHC/medium-ZHC. This study demonstrated that hydroxy compounds are potential alternatives for replacing sulphate supplements in broiler diets. Moreover, among the Cu and Zn levels, the low CHC (15 mg/kg) and medium ZHC (100 mg/kg) improved bone development and skin integrity, suggesting that the combination of Cu and Zn can be a nutritional strategy to prevent the incidence of leg disorders in broilers.
Keywords: bone health; hydroxychloride; leg disorders; sources; trace minerals